Paravaginal female adnexal tumor of probable Wolffian origin. A case report - Basheska, Neli; Yashar, Genghis; Kubelka, Katerina; Zografski, George; Stavrik, George (Springer, 1999)
Female adnexal tumor of probable Wolffian origin (FATWO) is a rare neoplasm originating from mesonephric remnants. Approximately 50 cases have been reported, predominantly arising in broad ligament, mesosalpinx, ovarian hilus, and periadnexal region. Aims: The aim of this report is to present the clinical and pathological features of a FATWO occurring in paravaginal area. So far, there have been only two cases reported to occur at this site. Case report: The patient is a 23-year old, nuliparous female, presented with a painless fixed paravaginal tumor. In August 1995, explorative laparatomy was performed. Encapsulated ovoid, tumor, located between urinary bladder and vagina, tightly fixed to vaginal wall connective tissue, was found. The uterus and both adnexa appeared unremarkable. The tumor was removed and biopsy sample from left ovary was taken. The patient had had an uneventful post-operative course and she remained well, without evidence of recurrence, 42 months after laparatomy. Results: The tumor was a solid ovoid mass with smooth surface, measuring 6.7 x 5 x 3.7 cm. On sectioning, the neoplastic tissue was solid, soft, butter yellow in colour; multiple cysts varying up to 3 cm in diameter and hemorrhagic foci were also present. Microscopically, it was well circumscribed and surrounded by fibrous capsule, composed of tumor cells arranged in different patterns: solid, closely packed tubules, and microcystic. The histochemical and immunohistochemical features of the tumor were identical to other cases of FATWO reported in the literature. Conclusions: Although the majority of these tumors are benign, a few cases have shown definite low malignant potential, with metastases and recurrences developing after at least 6 to 16 years following radical surgery. The presented case indicates that in spite of the unusual location, FATWO must be recognized, ensuring a careful and prolonged follow-up.
Keywords: female adnexal tumor of probable Wolffian origin; paravaginal; histopathology; immunohistochemistry; prognosis